Aberrant Expression and Subcellular Localization of PER2 Promote the Progression of Oral Squamous Cell Carcinoma. (24th February 2020) - Guo, Fengyuan; Tang, Qingming; Chen, Guangjin; Sun, Jiwei; Zhu, Junyi; Jia, Yulin; Zhang, Wenfeng
Abstract : Oral squamous cell carcinoma, one of the most prevalent cancer types in the world, has been confirmed under the influence of a key circadian gene, PER2, whose role has been identified in the development of some other types of cancers. However, the mechanism through which PER2 regulates the progress of OSCC remains largely unknown. In this study, we showed that besides the abnormal expression and subcellular localization of PER2 observed in OSCC tissues and cells as expected, these anomalous changes also existed in the adjacent noncancerous tissues, which was a novel finding in our research. The phase of PER2 rhythmic expression pattern in OSCC cells was later than that in oral keratinocytes in the protein level. In addition, we demonstrated that PER2 played as a resistant factor in the development of OSCC by upregulating TP53 and inhibiting epithelial-mesenchymal transition in vitro and in vivo . Taken together, our results identified that the development of OSCC is closely associated with PER2, the aberrant expression and subcellular localization of which facilitates the malignant progress.